# Calculator search results

Formula
Solve the equation
$3x+ \gamma = 6$
$x = - \dfrac { 1 } { 3 } \gamma + 2$
 Solve a solution to $x$
$3 x \color{#FF6800}{ + } \color{#FF6800}{ \gamma } = 6$
 Move the rest of the expression except $x$ term to the right side and replace the sign 
$3 x = 6 \color{#FF6800}{ - } \color{#FF6800}{ \gamma }$
$3 x = \color{#FF6800}{ 6 } \color{#FF6800}{ - } \color{#FF6800}{ \gamma }$
 Organize the expression 
$3 x = \color{#FF6800}{ - } \color{#FF6800}{ \gamma } \color{#FF6800}{ + } \color{#FF6800}{ 6 }$
$\color{#FF6800}{ 3 } \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ \gamma } \color{#FF6800}{ + } \color{#FF6800}{ 6 }$
 Divide both sides by the same number 
$\color{#FF6800}{ x } = \left ( \color{#FF6800}{ - } \color{#FF6800}{ \gamma } \color{#FF6800}{ + } \color{#FF6800}{ 6 } \right ) \color{#FF6800}{ \div } \color{#FF6800}{ 3 }$
$x = \left ( - \gamma + 6 \right ) \color{#FF6800}{ \div } \color{#FF6800}{ 3 }$
 Convert division to multiplication 
$x = \left ( - \gamma + 6 \right ) \color{#FF6800}{ \times } \color{#FF6800}{ \dfrac { 1 } { 3 } }$
$x = \left ( \color{#FF6800}{ - } \color{#FF6800}{ \gamma } \color{#FF6800}{ + } \color{#FF6800}{ 6 } \right ) \color{#FF6800}{ \times } \color{#FF6800}{ \dfrac { 1 } { 3 } }$
 Multiply each term in parentheses by $\dfrac { 1 } { 3 }$
$x = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 1 } { 3 } } \color{#FF6800}{ \gamma } \color{#FF6800}{ + } \color{#FF6800}{ 6 } \color{#FF6800}{ \times } \color{#FF6800}{ \dfrac { 1 } { 3 } }$
$x = - \dfrac { 1 } { 3 } \gamma + \color{#FF6800}{ 6 } \color{#FF6800}{ \times } \color{#FF6800}{ \dfrac { 1 } { 3 } }$
 Calculate the product of rational numbers 
$x = - \dfrac { 1 } { 3 } \gamma + \color{#FF6800}{ 2 }$
$\gamma = - 3 x + 6$
 Solve a solution to $\gamma$
$\color{#FF6800}{ 3 } \color{#FF6800}{ x } + \gamma = 6$
 Move the rest of the expression except $\gamma$ term to the right side and replace the sign 
$\gamma = 6 \color{#FF6800}{ - } \left ( \color{#FF6800}{ 3 } \color{#FF6800}{ x } \right )$
$\gamma = \color{#FF6800}{ 6 } \color{#FF6800}{ - } \left ( \color{#FF6800}{ 3 } \color{#FF6800}{ x } \right )$
 Organize the expression 
$\gamma = \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 6 }$
Solution search results